Counterparty Responses to Managerial Overconfidence - HRIBAR, Paul (Institutional Knowledge at Singapore Management University, 2013)
Existing research links CEO overconfidence to a number of corporate decisions including overinvestment, external acquisitions, and earnings management. These findings raise the question of whether counterparties distinguish between differences in CEOs, and how they respond to it. We focus on two key counterparties – auditors and credit rating agencies – and examine whether audit fees and credit ratings are affected by CEO overconfidence. We find a positive association between audit fees and CEO overconfidence, suggesting that auditors exert more effort or increase the risk premium associated with auditing firms with more overconfident CEOs. We also find a significant negative association between CEO overconfidence and credit ratings, suggesting that overconfident CEOs are associated with higher agency costs of debt and higher credit risk.